EVALUATION OF TOOTH SIZE DISCREPANCY IN DIFFERENT MALOCCLUSION GROUPS - Batool, Iffat; Abbas, Assad; Rizvi, S. Ausaf Ali; Abbas, Irum (Journal of Ayub Medical College Abbottabad, 2008)
Background: Orthodontic diagnosis and treatment planning requires the patient’s thorough history, extra and intra oral examination, analysis of diagnostic records comprising of orthodontic photographs, necessary radiographs and properly trimmed study casts. Tooth-size is the sum of mesio distal widths of the maxillary and mandibular teeth. For ideal occlusion, teeth in both arches should be proportional in size. If larger teeth in one jaw are occluded with smaller teeth in the other jaw, ideal occlusion is not achieved. Tooth size analysis was presented by Bolton in 1958. The ratio for anterior segment was derived to be 77.2±0.22% and 91.3±0.26% for the whole arch. Methods: A quantitative study was carried out at the Armed Forces Institute of Dentistry (AFID), Rawalpindi, Pakistan, a tertiary care facility. Cross sectional data was gathered from the study casts of patients undergoing orthodontic treatment at AFID, after obtaining informed written consent from them. 135 out of 200 study casts were filtered based upon the inclusion and exclusion criteria. ANB angle and witt’s appraisal were traced on corresponding lateral cephalograms. The mesio distal widths of all maxillary and mandibular teeth from right first molar to left first molar were calibrated with the use of a manual caliper. The readings were then used to compute the anterior and total Bolton ratios. Results: Significantly higher mean anterior tooth ratios were found for Class II (p<0.01) patients. All other ratios were within close range of Bolton’s norms. Conclusions: Skeletal Class II patients showed a tendency towards higher mesiodistal widths of teeth in the mandibular anterior region. Keywords: Interarch tooth size discrepancy, Bolton’s norms, Skeletal Class I, II and III